2014
DOI: 10.1155/2014/378024
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Hyaluronic Acid Migrates into the Skin of Rats

Abstract: Hyaluronic acid is a constituent of the skin and helps to maintain hydration. The oral intake of hyaluronic acid increases water in the horny layer as demonstrated by human trials, but in vivo kinetics has not been shown. This study confirmed the absorption, migration, and excretion of 14C-labeled hyaluronic acid (14C-hyaluronic acid). 14C-hyaluronic acid was orally or intravenously administered to male SD rats aged 7 to 8 weeks. Plasma radioactivity after oral administration showed the highest level 8 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Although our data from Kupffer cells indicates that HA35 has direct effects on inflammatory signaling in Kupffer cells, it is also possible that HA35 treatment in mice during ethanol feeding has direct and/or indirect protective effects on the intestine. Dietary HA is absorbed and migrates to the skin and other organs, and is then excreted in the urine and feces . In differentiated Caco‐2 monolayers, HA crosses the cell barrier in a size‐dependent manner, with smaller HA fragments having increased permeability .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our data from Kupffer cells indicates that HA35 has direct effects on inflammatory signaling in Kupffer cells, it is also possible that HA35 treatment in mice during ethanol feeding has direct and/or indirect protective effects on the intestine. Dietary HA is absorbed and migrates to the skin and other organs, and is then excreted in the urine and feces . In differentiated Caco‐2 monolayers, HA crosses the cell barrier in a size‐dependent manner, with smaller HA fragments having increased permeability .…”
Section: Discussionmentioning
confidence: 99%
“…In differentiated Caco‐2 monolayers, HA crosses the cell barrier in a size‐dependent manner, with smaller HA fragments having increased permeability . Radiolabeled HA studies in rats show that oral administration of HA lead to excretion in feces as well accumulation of HA in the skin with some residual in the blood up to 96 hours after treatment . However, the specific dynamics of HA35 absorption and metabolism are not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA is marketed as food supplement in the USA, Canada, Europe and Asia (particularly in Korea and Japan) with some difference in the suggested use: to treat joint pain in USA and in Europe; to treat wrinkle and to moisturize in Japan, even if the involvement of this polymer in the skin moisture retention effect needs to be further elucidated in the future [252]. In the present review, we focused our attention prevalently on studies that exclude complex mixtures, in order to evidence just HA effects; however, several researches describe the use of HA as food ingredient in enriched extracts or mixtures with collagen and other supplements.…”
Section: Cosmeticsmentioning
confidence: 99%
“…Thus, combining HA oral treatment with HA topical and injective administration could be very succesfull in the control of skin ageing. A further study suggesting that orally administered HA can migrate into the skin of rats, thus possibly reducing skin dryness, was conducted by Oe et al, who demonstrated that about the 90% of the ingested HA was absorbed from the digestive tract and was used as an energy source or a structural component [252].…”
Section: Cosmeticsmentioning
confidence: 99%